Dancing into the Third Age Social Dance as Cultural Text - Research in Progress - Thomas, Helen; Cooper, Lesley (Edinburgh: Edinburgh University Press, 2002)
RESUMEN: This paper centres on a discussion of an on-going one-year qualitative research project, which seeks to assess the meanings of social dance of groups of participants who are entering or have entered what has come to be known as the "third age". The research focuses on people around the age of 60 and above who participate in dance events in two inner city, south-east London boroughs and in the country of Essex to the east and north of London, where the majority of those who take part are from the older age-ranges. Lesley Cooper and Helen Thomas are conducting research. As the project at the time of writing is just over halfway through, the discussion that follows may be seen as a preliminary account of the research so far.